Estetika Al-Kinayah dan Konstruksi Gender dalam Ayat-Ayat Seksualitas Al-Qur'an: Kajian Balaghah Tafsir - Nurlelah Nurlelah; Rahmi Damis; Rosmini Rosmini (Universitas 45 Surabaya, 2026)
This study examines the aesthetics of al-kinayah (rhetorical circumlocution) in Qur'anic verses on sexuality and its implications for the construction of gender relations. Discourse on these verses tends to fall into two extremes: treated as taboo, or read literally in ways that produce patriarchal bias, as seen in readings of ḥarth (tillage) in QS al-Baqarah/2:223, often understood as legitimizing male dominance over women's bodies. Prior research has largely approached these verses through fiqh and family law, while their rhetorical (balaghah) dimension has rarely been connected specifically to gender studies. This article addresses that gap by examining how the choice of kinayah shapes rather than merely conceals reciprocal gender relations. The study employs a qualitative-descriptive library research method, with kinayah theory within ilmu bayan and gender theory as its formal object, and sexuality-related verses such as lamastum, mubāsyarah, al-rafats, and libās as its material object. The findings show that kinayah serves a dual function: safeguarding public linguistic propriety while simultaneously structuring a reciprocal relationship between men and women, as reflected in the